Penerapan Pathfinding Menggunakan Algoritma A* Pada Non Player Character (NPC) Di Game - Paulus Harsadi; Sri Siswanti (STMIK Sinar Nusantara, 2019)
In this Game , we implement a character designer at the enemy by applying the algorithm A * pathfinding Algorithm. Furthermore, A * is as the algorithm for searching solutions with the use of additional information (heuristics) in which it is an optimal solution. The purpose of developing this Adventure Game is A * Algorithm implementation for Pathfinding using Unity 3D. Pathfinding is the fastest path of searching process from point of origin to point of destination by avoiding the various barriers along the path traveled without crashing the existing barrier along the way. Its design and development applies Unity 3D. The test result of algorithm in the Game shows that the total of passed node result is 50 nodes. It is similar with the previous manual count result. Furthermore, the Game route shows that its passed path is similar with manual count.